Innovation Technologies in Green Buildings and Certification - Özata, Şerife; Girgin, Zehra Canan (ICONARCH International Congress of Architecture and Planning, 2014)
For a sustainable world, recent awareness depending on the depletion of the Earth’s fossil resources and global warming due to high CO2 emissions has impacted building design and construction methods; thereby the green or ecological building concept has emerged. In order to evaluate and categorize green buildings, some evaluation systems were constituted. One of them is accredited LEED certification system (Leadership in Energy and Environmental Design). LEED has silver, gold and platinum certification levels classifying the characteristics of green buildings. In the stages of design, construction and service life, the sustainable building design should satisfy the prerequisites of LEED certification system on sustainable site development, water savings, energy efficiency, materials and resources selection, and indoor environmental quality. The renewable energy sources (wind, solar, geothermal heat pump etc.), efficient lighting, recycling/reuse of resources and materials, and waste recycling should be maximized to ensure the low environmental impact in building technologies. In this study, typical current and innovative technologies in the design of ecological buildings are handled by referring the buildings having LEED certification on different levels.